Facilitators' teaching and social presence in online asynchronous interprofessional education discussion. Issue 4 (3rd July 2020) - Evans, Sherryn; Knight, Tess; Walker, Arlene; Sutherland-Smith, Wendy
ABSTRACT: Asynchronous discussion boards have been increasingly used to engage teams of interprofessional learners in interactive and reflective discourse. Facilitation of this interprofessional discourse is critical, yet largely unexplored. The Community of Inquiry (CoI) framework provides a lens through which facilitators' contributions on asynchronous discussion boards can be explored. The aim of this study was to apply the CoI framework teaching and social presence indicators to an online asynchronous IPE facilitation environment to determine if they comprehensively describe the kind of contributions made by IPE facilitators in two types of interprofessional team discussions. Directed content analysis based on the teaching and social presence indicators from the CoI framework was used to analyse seven facilitators' contributions to four asynchronous team discussion points (two key dimensions and two case study discussions). Sixteen of the 31 teaching and social presence indicators, along with a new indicator (feedback on assessment tasks), comprehensively described the facilitators' contributions. Many of the teaching presence indicators were used in a greater proportion of the key dimension discussions than in the case study discussions. This study demonstrates that the teaching and social presence indicators of the CoI framework are a valuable way to describe the contributions made by facilitators to asynchronous interprofessional team discussions.